Lipoprotein-Associated Phospholipase A2 Activity increase the Sensitivity of Framingham Score for detecting the incidence of Acute Myocardial Infarction in sub-population of Indonesian Male Patients - Andi Wahjono; Saifur Rohman; Miryanti Cahyaningtias; Rina Yudha; Yanna Indrayana; Mifetika lukitasari; Rusdianto Rusdianto; Aditya Kurniawan; Djanggan Sargowo; Sasmojo Widito; Dadang Hendrawan; Jayarani Fatimah Putri; widodo Ph.D (Journal of Global Pharma Technology, 2017)
Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an inflammatory biomarker of cardiovascular disease. Framingham score is currently a widely used risk stratification tool for detecting the incidence of acute myocardial infarction (AMI), although it is not very sensitive. Adding Lp-PLA2 to the Framingham score can raise the odds ratio (OR) for AMI, but requires further research.Objectives: In this study, we examine the role of Lp-PLA2 in increasing the sensitivity of the Framingham score for detecting the incidence of AMI.Methods: This study was a case-control study of 97 male patients, 60 of whom had AMI and were treated in the intensive care unit as test subjects, and 37 of whom were non-AMI patients with normal treadmill test used as controls.Results:Lp-PLA2 activity was found to be higher in the AMI group than that in the control group (83.97 ± 27.15 nmol/ml/min vs. 55.04 ± 31.99 nmol/ml/min). Eighteen patients (30%) with AMI were included in the high-risk category according to the Framingham score; this number increased to 36 patients after the addition of Lp-PLA2 activity to the Framingham score. Analysis using a receiver operating characteristic (ROC) showed a cut-off value for Lp-PLA2 activity associated with AMI of approximately 74.21 nmol/ml/min with an accuracy of 67%. The OR for detecting AMI incidence increased after the addition of Lp-PLA2 activity from 1:01 (CI 95%, 0.414–2.48) to 4.67 (CI 95%, 1.88-11.61).Conclusions: The addition of Lp-PLA2 activity may increase the sensitivity of the Framingham score for detecting the incidence of AMI.